EVALUASI KINERJA PENGAWASAN PAJAK REKLAME DI KABUPATEN SIDOARJO (STUDI PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET KABUPATEN SIDOARJO) - TRI HATMOKO, ASWIN (Jurnal Akuntansi AKUNESA, 2016)
The purpose of this study was to evaluate the job of tax supervision mobile billboards in Sidoarjo. The study was based on the basis of the conditions in the field where there are many damaged mobile billboards in the district of Sidoarjo that are still set on the vehicle. This study used a qualitative approach with interviews and documentation data collection methods. Data were analyzed using triangulation and theory. The study concluded that the job done by a team of billboards in Sidoarjo has not done well. It is caused by established procedures for doing supervisory functions billboards is less effective, object of the supervision is not appropriate when using guideline rules for incidental billboards used to control mobile billboard, and no follow-up of police as SKPD who have the authority to curb if there are mobile billboards that violate the regulations on the administration of the billboard.  Keywords: Tax, Mobile Billboards, Evaluation, Monitoring